2013
DOI: 10.1002/stem.1376
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Receptor A Signaling Regulates Stem Cell Recruitment and Angiogenesis: A Model to Study Linkage Between Inflammation and Tumorigenesis

Abstract: Natriuretic peptide receptor A (NPRA), the signaling receptor for the cardiac hormone, atrial natriuretic peptide (ANP), is expressed abundantly in inflamed/injured tissues and tumors. NPRA deficiency substantially decreases tissue inflammation and inhibits tumor growth. However, the precise mechanism of NPRA function and whether it links inflammation and tumorigenesis remains unknown. Since both injury repair or tumor growth require stem cell recruitment and angiogenesis, we examined the role of NPRA signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
0
18
0
1
Order By: Relevance
“…NPRA is a transmembrane receptor with guanylate cyclase (GC) activity that can synthesize cGMP, which mediates most of the biological effects of BNP such as diuresis, natriuresis, vasodilation, blood pressure reduction, regulation of body fluid volume, and maintenance of electrolyte balance . Recently, NPRA signalling was reported to have a significant role in inflammation‐induced angiogenesis as assayed by endothelial sprouting . In addition, atrial natriuretic peptide/NPRA signalling was shown to induce a predominantly Th2‐type response to activate pathological processes during acute allergic asthma .…”
Section: Discussionmentioning
confidence: 99%
“…NPRA is a transmembrane receptor with guanylate cyclase (GC) activity that can synthesize cGMP, which mediates most of the biological effects of BNP such as diuresis, natriuresis, vasodilation, blood pressure reduction, regulation of body fluid volume, and maintenance of electrolyte balance . Recently, NPRA signalling was reported to have a significant role in inflammation‐induced angiogenesis as assayed by endothelial sprouting . In addition, atrial natriuretic peptide/NPRA signalling was shown to induce a predominantly Th2‐type response to activate pathological processes during acute allergic asthma .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF, EGF). Furthermore, secretion of angiogenic factors in injured tissue could be due to the activation of HIFs [Mallela et al, 2013]. MSCs can also recruit the other MSCs or progenitor cells towards the injury/defect site via paracrine effects [Shao et al, 2015].…”
Section: Msc Homing and Recruitment To Bone Defectsmentioning
confidence: 99%
“…The NPR-A has been reported to be expressed in various types of cancer, such as lung cancer, ovarian cancer, gastric cancer and prostate cancer [117119]. Another study shows the involvement of NPR-A in lung cancer-induced vascular endothelial growth factor (VEGF) expression and angiogenesis [118].…”
Section: Roles Of Natriuretic Peptides In Metabolic Syndromementioning
confidence: 99%